Etiological Profile of Epilepsy in Patients at a Tertiary Care Hospital: An Observational Study: Etiological Profile of Epilepsy in Patients at a Tertiary Care Hospital - Arshad, Waleed; Khan, Shahbaz; Nizamani, Samahir Akram; Bughio, Abdul Hafeez; Lakhair, Manzoor Ali (Pakistan Journal of Health Sciences, 2026)
Epilepsy has diverse etiologies that vary by age, gender, and region. Identifying the cause is essential for management and prognosis. Objectives: To determine the etiological profile of epilepsy in patients at a tertiary care hospital and assess associations with age and gender. Methods: This observational study was conducted in the Department of Neuro-medicine, Liaquat University of Medical and Health Sciences, Jamshoro, from March 15 to September 14, 2022. A total of 156 patients aged ≥18 years with epilepsy for over five years were enrolled by consecutive sampling. Those with acute symptomatic seizures or incomplete records were excluded. Etiologies were classified using International League Against Epilepsy 2017 criteria based on electroencephalography and magnetic resonance imaging. Results: A total of 156 adult epilepsy patients were included (mean age 54.7 ± 15.6 years; 101 male, 55 female). Acute ischemic stroke was the most common etiology, 74 (47.4%), followed by idiopathic epilepsy, 29 (18.6%), brain tumors, 15 (9.6%), traumatic brain injury, 13 (8.3%), intracerebral hemorrhage, 10 (6.4%), CNS infections, 8 (5.1%), and encephalitis, 11 (7.1%). A higher proportion of female was observed within the brain tumor and idiopathic epilepsy subgroups, 10 (66.7%) and 19 (65.5%), respectively (p < 0.05); however, these findings reflect distribution within the tertiary cohort and should not be interpreted as population-level risk. Insignificant associations were found between etiology and age group or epilepsy duration. Conclusions: Acute ischemic stroke was the leading cause of epilepsy, with significant gender differences for brain tumors and idiopathic epilepsy.